-4z-5z=-5z-7+3z

Simple and best practice solution for -4z-5z=-5z-7+3z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4z-5z=-5z-7+3z equation:


Simplifying
-4z + -5z = -5z + -7 + 3z

Combine like terms: -4z + -5z = -9z
-9z = -5z + -7 + 3z

Reorder the terms:
-9z = -7 + -5z + 3z

Combine like terms: -5z + 3z = -2z
-9z = -7 + -2z

Solving
-9z = -7 + -2z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '2z' to each side of the equation.
-9z + 2z = -7 + -2z + 2z

Combine like terms: -9z + 2z = -7z
-7z = -7 + -2z + 2z

Combine like terms: -2z + 2z = 0
-7z = -7 + 0
-7z = -7

Divide each side by '-7'.
z = 1

Simplifying
z = 1

See similar equations:

| (7/8)+(1/7)(y-8)=(y+1)/(5) | | 55=(9/5)(300-273)+32 | | 5/2x-1=-1 | | (2/1)/(1/3) | | 32x^4+16x^3-80x^2=0 | | 7(x+9)=8(x-1) | | -3a^-2b^3/15a^-7b^-1 | | 33x^2-32x-585=0 | | -4(6y-6)-y=-4(y-5) | | b/8+1/3=19 | | f(x)=3(2+2)-4 | | 4(2-(1/8)p)=(1/4)p-7 | | x^2-10x+21=(x-7)(x+3) | | 6n+6/9=12 | | 3x-5+7=2x-9 | | 15s^2-8s+1=0 | | 9x+5(35-x)=287 | | 6(3x+1)=3x-9X | | 1/4x+4=y | | y^3=-21 | | -12x+2(x-5)+9x=3x-10 | | x+y=15andx-2 | | -3.5=x/7 | | 8b-9y/4b-b-5y/4b | | b-9y/4b-b-5y/4b | | 8b-9y/4b-b-5y/4b=0 | | 2x^3-1-1=0 | | 20+3m+6m=92 | | -52^1/2 | | 11/2d=8 | | 1/5(10x-4)=7 | | -11/2d |

Equations solver categories